(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The objective of the investigation was to determine the impact of SAQ training on the physical well-being of football and hockey athletes. For this investigation, forty (40) state level football athletes aged between 14-16 years were randomly chosen from Golden Star football club Kheri, Talwana. The participants were haphazardly divided into two categories as the experimental cohort (soccer athletes) and the control cohort. The exploratory group underwent a SAQ training regimen while no training was given to the control group. The duration of instruction was six weeks in a timetable of weekly three days for every other day. The information were gathered based on the chosen bodily health factors prior to and following the exercise duration. The information that was gathered was examined by "t" examination and the degree of importance was established at 0.05 level. Data examination revealed noteworthy enhancement in the speed, nimbleness, and robustness of the football athletes.